Pengurusan disiplin sekolah menegah kebangsaan harian di daerah Pasir Gudang, Johor - Mohamed Nor, Salwana (2013)
This study aimed to determine the knowledge and skills of teacher discipline in carrying out the task of managing school discipline in secondary schools in the district of Pasir Gudang. A total of 100 respondents from the selected discipline teachers from 10 schools in the Pasir Gudang zone to represent the school in Pasir Gudang. The research instrument using questionnaires have been endorsed by the supervisor. Survey instrument was distributed to 10 respondents as a pilot study to test the reliability / validity analysis. The reliability (Cronbach alpha) for the instruments used in this study was 0.79 for the set of questions the knowledge and the skills is 0.94. Were analyzed using the software "Statistical Package for the Social Sciences 'version 16.0'. Descriptive data analysis performed (mean, frequency and percentage) and inferential (t-test and Correlasion). The study found that the level of discipline knowledge and skills of teachers in secondary schools Pasir Gudang district is high. In addition there is a significant relationship between teachers 'knowledge and skills in the discipline but there is no significant relationship between teachers' knowledge and skills in the discipline of teacher gender..